Self‐rated health scores predict mortality among people with type 2 diabetes differently across three different country groupings: findings from the ADVANCE and ADVANCE‐ON trials - Hua, X. (Diabet Med, 2020)
AIMS: To explore whether there is a different strength of association between self‐rated health and all‐cause mortality in people with type 2 diabetes across three country groupings: nine countries grouped together as 'established market economies'; Asia; and Eastern Europe. METHODS: The ADVANCE trial and its post‐trial follow‐up were used in this study, which included 11 140 people with type 2 diabetes from 20 countries, with a median follow‐up of 9.9 years. Self‐rated health was reported on a 0–100 visual analogue scale. Cox proportional hazard models were fitted to estimate the relationship between the visual analogue scale score and all‐cause mortality, controlling for a range of demographic and clinical risk factors. Interaction terms were used to assess whether the association between the visual analogue scale score and mortality varied across country groupings. RESULTS: The visual analogue scale score had different strengths of association with mortality in the three country groupings. A 10‐point increase in visual analogue scale score was associated with a 15% (95% CI 12–18) lower mortality hazard in the established market economies, a 25% (95% CI 21–28) lower hazard in Asia, and an 8% (95% CI 3–13) lower hazard in Eastern Europe. CONCLUSIONS: Self‐rated health appears to predict 10‐year all‐cause mortality for people with type 2 diabetes worldwide, but this relationship varies across groups of countries.